Systematic Violence against Human Rights Defenders of the Environment and Territory within the Post-agreement Framework in Colombia - Turriago-Molinas, Andrea (Acciones e Investigaciones Sociales, 2022)
This article examines the general context of human rights defenders of the environment and territory in Colombia based on a review of the literature, from a documented perspective, analysing the exercise of defending the environment in a violent situation. The study takes as its starting point the disputes over natural resources that are accompanied by significant negative impacts both at a social and environmental level. Efforts to attempt to protect the environment and most vulnerable communities have given rise to the so-called environmental defenders, who assume responsibility for safeguarding the rights of both human beings and also those of the land. This defensive exercise in Colombia has very special characteristics, such as armed conflict and structural violence, within which a series of systematic violent practices perpetrated against them can be identified. Such aspects complicate their defence of the environment and increase the level of vulnerability of such communities, making the task of these defenders even more difficult.